2005
DOI: 10.5194/acpd-5-13011-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Balloon-borne stratospheric BrO measurements: comparison with Envisat/SCIAMACHY BrO limb profiles

Abstract: Abstract. For the first time, results of all four existing stratospheric BrO profiling instruments, are presented and compared with reference to the SLIMCAT 3-dimensional chemical transport model (3-D CTM). Model calculations are used to infer a BrO profile validation set, measured by 3 different balloon sensors, for the new Envisat/SCIAMACHY (ENVIronment SATellite/SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY) satellite instrument. The balloon observations include (a) balloon-borne in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…8 for contributions of 6 pptv (cyan dashed line) and 8 pptv (blue dashed line) from the decomposition of the short-lived bromine species. The value of 8 pptv can be considered as a plausible upper limit for the contribution of the bromine short-lived species, in agreement with recent studies Salawitch et al, 2005;Schofield et al, 2006;Dorf et al, 2006a, b;Sioris et al, 2006). This also confirms the findings of Feng et al (2007), who have tested different methods of implementing the bromine source gases in the SLIMCAT model and found that the agreement between model and balloon data is significantly improved when having explicitly the short-lived source gases.…”
Section: Stratospheric Brosupporting
confidence: 78%
See 2 more Smart Citations
“…8 for contributions of 6 pptv (cyan dashed line) and 8 pptv (blue dashed line) from the decomposition of the short-lived bromine species. The value of 8 pptv can be considered as a plausible upper limit for the contribution of the bromine short-lived species, in agreement with recent studies Salawitch et al, 2005;Schofield et al, 2006;Dorf et al, 2006a, b;Sioris et al, 2006). This also confirms the findings of Feng et al (2007), who have tested different methods of implementing the bromine source gases in the SLIMCAT model and found that the agreement between model and balloon data is significantly improved when having explicitly the short-lived source gases.…”
Section: Stratospheric Brosupporting
confidence: 78%
“…Based on a budget of the long-lived natural (CH 3 Br) and anthropogenic (CH 3 Br, CBrClF 2 , CBrF 3 , CBrF 2 CBrF 2 , CBr 2 F 2 ) organic bromine source gases observed over the last decade (Wamsley et al, 1998), the stratospheric Br y loading is currently estimated to be about 16-17 pptv. However, several recent studies Salawitch et al, 2005;Sioris et al, 2006;Sinnhuber et al, 2002Sinnhuber et al, , 2005Schofield et al, 2004a;Dorf et al, 2006a, b) have suggested that an additional contribution of about 5.6±2 pptv must be considered, due to bromine release from short-lived biogenic organic compounds (such as CHBr 3 , CH 2 Br 2 , CH 2 BrCl, CHBr 2 Cl, CHBrCl 2 , CH 2 BrCH 2 Br) or even the direct intrusion of inorganic bromine from tropospheric origin into the lower stratosphere. Inorganic bromine compounds may be produced and sustained in the free troposphere due to the decomposition of short-lived organic bromine compounds under the action of heterogeneous and/or gas-phase photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BrO fitting window is fixed to 332-370 nm. More details on the instrument and the retrieval algorithm can be found in Pundt et al (2002) and Dorf et al (2006b). As for the SAOZ balloon, the LPMA/DOAS balloon uses the solar occultation technique.…”
Section: Comparison To Saoz and Lpma/doas Balloon Profilesmentioning
confidence: 99%
“…The BrO DOAS evaluation is performed in the 346-360 nm wavelength range and vertical profiles are retrieved using the OEM. A detailed description of the LPMA/DOAS BrO measurements can be found in Harder et al (1998 and and Dorf et al (2006b). Due to the variation of the SZA during the ascent of the balloon, a photochemical correction, calculated by using the photochemical model PSCBOX, is applied to the groundbased profiles in order to take into account this photochemical effect.…”
Section: Comparison To Saoz and Lpma/doas Balloon Profilesmentioning
confidence: 99%